Polynomial Approach and Non-linear Analysis for a Traffic Fundamental Diagram - Rosas-Jaimes, Oscar A.; Téllez, Luis Alberto Quezada; Anaya, Guillermo Fernández (Promet - Traffic&Transportation, 2016)
Vehicular traffic can be modelled as a dynamic discrete form. As in many dynamic systems, the parameters modelling traffic can produce a number of different trajectories or orbits, and it is possible to depict different flow situations, including chaotic ones. In this paper, an approach to the wellknown density-flow fundamental diagram is suggested, using an analytical polynomial technique, in which coefficients are taken from significant values acting as the parameters of the traffic model. Depending on the values of these parameters, it can be seen how the traffic flow changes from stable endpoints to chaotic trajectories, with proper analysis in their stability features.